POU2F1 Promotes Cell Viability and Tumor Growth in Gastric Cancer through Transcriptional Activation of lncRNA TTC3-AS1. (29th June 2021) - Wang, Jixu; Xiao, Ke; Hou, Futao; Tang, Lusheng; Luo, Dan; Liu, Gu; Wang, Zhiqiang
Abstract : POU domain, class 2, transcription factor 1 (POU2F1) is involved in the development of gastric cancer (GC). However, the molecular mechanism has not been fully elucidated. Here, we identified a novel lncRNA named TTC3-AS1 that was potentially regulated by POU2F1 and investigated their roles in GC progression. Bioinformatics analysis suggested that high expression of POU2F1 predicted poor prognosis in patients with GC. We further screened out an lncRNA TTC3-AS1 that may be transcriptionally activated by POU2F1 according to the JASPAR database, and POU2F1 and TTC3-AS1 were highly expressed in GC cells and tissues compared with normal controls (NCs). Function analysis revealed that both POU2F1 and TTC3-AS1 played oncogenic roles by promoting cell viability, migration, and invasion in GC. qRT-PCR analysis showed that POU2F1 improved the expression of TTC3-AS1 in GC cells, while TTC3-AS1 knockdown or overexpression had no effect on POU2F1 expression. The results of chromatin immunoprecipitation and DNA-affinity precipitation assays indicated that POU2F1 directly bound to the promoter region of TTC3-AS1 and activated its transcription. TTC3-AS1 knockdown neutralized the protumor effects of POU2F1 overexpression in GC cell lines as well as mouse models of GC, which suggested that TTC3-AS1 mediates the oncogenic function of POU2F1. In summary, POU2F1 promoted GC progression by transcriptionally activating TTC3-AS1; thus, this study provided a new perspective for the mechanism of GC progression.